Morphological and Functional Differences between Athletes and Novices in Cortical Neuronal Networks - Tan, Xiao-Ying; Pi, Yan-Ling; Wang, Jue; Li, Xue-Pei; Zhang, Lan-Lan; Dai, Wen; Zhu, Hua; Ni, Zhen; Zhang, Jian; Wu, Yin (Frontiers in Human Neuroscience, 2017)
The cortical structural and functional differences in athletes and novices were investigated with a cross-sectional paradigm. We measured the grey matter volumes and resting-state functional connectivity in 21 basketball players and 21 novices with magnetic resonance imaging techniques. It was found that grey matter volume in the left anterior insula, inferior frontal gyrus, inferior parietal lobule and right anterior cingulate cortex, precuneus is greater in basketball players than that in novices. These five brain regions were selected as the seed regions for testing the resting-state functional connectivity in the second experiment. We found higher functional connectivity in default mode network, salience network and executive control network in basketball players compared to novices. We conclude that the morphology and functional connectivity in cortical neuronal networks in athletes and novices are different.